Low-Emission Development Strategies (LEDS) Technical, Institutional and Policy Lessons - Clapp, Christa (OECD/IEA Climate Change Expert Group Papers, 2010)
The term low-emission development strategies (LEDS) first emerged under the United Nations Framework Convention on Climate Change (UNFCCC) in 2008 and its possible role in a future climate framework continues to be debated. Though no formally agreed definition exists, LEDS are generally used to describe forward-looking national economic development plans or strategies that encompass low-emission and/or climate-resilient economic growth. LEDS can serve multiple purposes but are primarily intended to help advance national climate change and development policy in a more co-ordinated, coherent and strategic manner. A LEDS can provide value-added to the myriad of existing climate change and development related strategies and reports that already exist by providing integrated economic development and climate change planning.